Analysis of Tax Avoidance Mediated by Profitability and Company Size as Moderating Variables (Case Study of Property and Real Estate Service Sector Companies Listed on the Indonesia Stock Exchange for the 2014-2018 Period): Analysis of Tax Avoidance Mediated by Profitability and Company Size as Moderating Variables (Case Study of Property and Real Estate Service Sector Companies Listed on the Indonesia Stock Exchange for the 2014-2018 Period) - Rita Andini; Mokhlas Mokhlas (Institute of Computer Science (IOCS), 2020)
One of the functions of taxes is to regulate and implement government policies in the social and economic fields and be used for the prosperity of the people, so the revenue must be maximized. Phenomenon of State Budget Revenues and Expenditures (APBN) up to December 26, 2019 in Indonesia, tax revenues reached Rp 1,266.65 trillion or 80.29% of the 2019 State Budget target of Rp 1,577.6 trillion or there was a difference of 19.71% from the target, there is a downward trend, so this must be considered by the handling system by the tax authorities. Some variables that are thought to influence tax avoidance by taxpayers include; Proportion of Independent Board of Commissioners, Institutional Ownership with Profitability as Mediation Variable and Company Size as Moderation Variable. In general, this study aims to examine, analyze whether the Proportion of Independent Commissioners, Institutional Ownership can partially influence Tax Avoidance, and how much direct, indirect influence through the profitability variable, and whether Company Size can strengthen it. Specifically this research aims to provide advice on the management of property and real estate companies listed on the Indonesia Stock Exchange in the 2014-2018 period, in terms of how to minimize tax payments. The population in this study is the property and real estate sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample in this study uses a purposive sampling method obtained as many as 75 companies that meet the criteria. Variables consist of five variables: Proportion of Independent Commissioners, Institutional Ownership as an independent variable, Profitability becomes a mediating variable, and Company Size as a moderating variable, while Tax Avoidance as a variable bound. The method of data analysis is done by hypothesis testing (t-test), path analysis, and moderating variable tests using MRA (Moderated Regression Analysis)